A world of many worlds - Cadena, Marisol de la 1957-; Blaser, Mario 1966- (Duke University Press, 2018)
A World of Many Worlds is a search into the possibilities that may emerge from conversations between indigenous collectives and the study of science's philosophical production. The contributors explore how divergent knowledges and practices make worlds. They work with difference and sameness, recursion, divergence, political ontology, cosmopolitics, and relations, using them as concepts, methods, and analytics to open up possibilities for a pluriverse: a cosmos composed through divergent political practices that do not need to become the same.Contributors. Mario Blaser, Alberto Corsín Jiménez, Déborah Danowski, Marisol de la Cadena, John Law, Marianne Lien, Isabelle Stengers, Marilyn Strathern, Helen Verran, Eduardo Viveiros de Castro